MEWUJUDKAN KEADILAN DALAM PEMBELAJARAN KELOMPOK: ANALISIS KETIDAKSEIMBANGAN PERAN DAN STRATEGI PENANGANANNYA DI SEKOLAH DASAR - Miftah Alfiah; Desi Fitria Sari; Nadya Aulia Sari; Siti Hotijah (STKIP Subang, 2025)
This research is motivated by the limited studies on role imbalance and group learning in elementary schools, even though this phenomenon has a significant impact on students' learning motivation, the effectiveness of teamwork and classroom dynamics. The purpose of this study is to analyze the factors that cause role imbalance in groups and identify strategies applied by teachers to create equity in the collaborative learning process. The method used was qualitative with a literature review approach, which involved analyzing various sources of scientific articles and academic publications from the last five years. The results of the study show that role imbalance in groups can affect learning motivation, group work outcomes and overall classroom dynamics. Students' roles in the group are also influenced by internal factors such as fine motor skills, motivation and learning habits. External factors such as parental attention and social environment are also included. These findings are in line with the research objectives and reinforce social learning theory which emphasizes the role of environment and social interaction in learning. The main conclusion of this study is the importance of implementing fair and adaptive group management strategies to create inclusive and effective learning. The implications of this research include theoretical aspects, such as enriching the literature on group learning dynamics. Keywords: Group learning, Equity, Student roles, Teacher strategies